On solvability of some boundary value problems for differential equations with "maxima" - Stepanov, Eugene (Topological Methods in Nonlinear Analysis, 1996)
The method of a priori estimates based on the Leray–Schauder topologicaldegree theory is developed to establish the existence of solutions to generalboundary value problems for differential equations with “maxima”.